Teaching Reading Comprehension to School Children With Autism Spectrum Disorders: Secrets From Experience - Aguiar-Aguiar, Giselvis (2020)
The essay reflects on the ways children with Autism Spectrum Disorders (ASD) can learn reading comprehension at school, based on the work experiences of the authors. It offers a set of ideas, from examples facilitating their use, that can help improve the work of teachers in charge of students with special educational needs due to ASD. Some novel ways offered are pairing and recoding from a visual pattern and structured routines based on the use of visual supports, based on the potential of the visual memory of these children.